NATURAL DEGASSING OF CARBON DIOXIDE AND HYDROGEN SULPHIDE AND ITS ENVIRONMENTAL IMPACT AT MILOS ISLAND, GREECE - Kyriakopoulos, G.K. (Bulletin of the Geological Society of Greece, 2010)
The Aegean region represents an active convergent zone, where continental micro-plates exhibit a complex interaction between the African and the Eurasian plates. The calc-alkaline volcanic activity of the Southern Aegean region developed in various volcanic centers from Soussaki to Nisyros through Methana-Poros, Milos and Santorini. Milos Island has been an active volcano till the middle of Quaternary and is at present characterized by a high enthalpy geothermal system. The volcanism started 3.5 Ma ago and still continues up today in the form of post-volcanic manifestations. Most quiescent volcanoes released large amounts of CO2 and H2S through fumarolic activity and soil diffuse degassing. Numerous small fumaroles occur in various places, mainly at Kalamos and Adamas volcanic areas. Also along the southern coast of the island there are volcanic gas manifestations in the sea. Gases were sampled from fumaroles at Kalamos area as well as from north east part of Adamas village. Furthermore many soil gases were sampled at 50 cm depth and analyzed for their chemical composition. Apart from atmospheric gases (N2 and O2), which sometimes contaminate the samples, the main gas phase is CO2. Sometimes also H2S, CH4 and H2 are present in high amounts while CO and He are always present in trace amounts. The He isotopic composition highlights a significant mantle component. CO2 and H2S concentrations higher than in the normal atmosphere can be stimulating for plant growth until certain levels and detrimental above them. As for many active geothermal areas of the world also H2S and CO2 concentrations measured in the area of Milos could be of concern for human health.